2020
DOI: 10.3389/fpubh.2020.00334
|View full text |Cite
|
Sign up to set email alerts
|

A Cross-Sectional Study of the Relationship Between Mental Health Problems and Overweight and Obesity in Adolescents

Abstract: Background: There is a suggested coexistence between obesity and mental health discomfort in adolescence. The objective of this study was to explore if mental health indices covaried with body mass index (BMI) in adolescence and if there were gender-related disparities. Methods: Data were collected in two cross-sectional surveys of 10th-grade students (15 to 16 years old) carried out in 2002 and 2017. The questionnaires included self-reported height and weight, questions covering mental health using the Streng… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
8
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 41 publications
(54 reference statements)
5
8
0
3
Order By: Relevance
“…According to the WHO, obesity is continuously growing worldwide and has tripled in the last forty years [1]. Its relationship with noninfectious diseases, e.g., diabetes, hypertension, dyslipidaemia and metabolic syndrome, reducing life expectancy and quality of life, are well known [2,3]. The revealed obesity-related markers presented in the literature have been widely reported.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…According to the WHO, obesity is continuously growing worldwide and has tripled in the last forty years [1]. Its relationship with noninfectious diseases, e.g., diabetes, hypertension, dyslipidaemia and metabolic syndrome, reducing life expectancy and quality of life, are well known [2,3]. The revealed obesity-related markers presented in the literature have been widely reported.…”
Section: Introductionmentioning
confidence: 99%
“…The revealed obesity-related markers presented in the literature have been widely reported. Among the mentioned markers, a sedentary lifestyle [4], socioeconomic factors [5], genetics [6], microbiome [7], psychological well-being [2], endocrine regulation [3], family and education influence [8,9], dietary behaviours such as skipping breakfast [10], snacking [11] and meal regulations [12][13][14] are prominent. Despite confirmed associations between obesity and its markers, there is a constant search for (and analysis of) new dependencies to manage and slow the 21st-century epidemic.…”
Section: Introductionmentioning
confidence: 99%
“…Klinik örneklemde obezlerde yapılan çalışmalarda dışa yönelim ve içe yönelimle ilgili bozuklukların; DEHB, depresyon bozukluğu olanlarda da aşırı kilolu olma ve obezitenin arttığını gösteren çalışmalar vardır [6-8, 67, 68]. Toplum örneklemli bir çalışmada ailenin doldurduğu GGA'ya göre akran sorunları ile BKİ arasında pozitif bir ilişki bulunmuş; kızlarda emosyonel sorunlar, erkeklerde davranım sorunları ile BKİ arasında ilişki tespit edilmiştir [14]. Ancak BKİ ya da aşırı kilolu/obez olma ile ruhsal sorunlar arasında hiçbir ilişki bulmayan [9,10] ya da akran sorunları dışında hiçbir ilişki belirlemeyen toplum örneklemli çalışmalar da vardır [69].…”
Section: Discussionunclassified
“…Çocukluk çağında obezitenin içe yönelim semptomlarıyla bağıntılı olduğuna dair hem kesitsel hem de izlemsel çalışmalardan elde edilen kanıtlar mevcuttur [12]. Normal BKİ olan olgulara göre aşırı kilolu/obez erkeklerde dışayönelim sorunları; kızlarda da içeyönelim sorunları daha fazla görülmektedir [13,14]. Türkiye'de ise çok az sayıda araştırma bu ilişkiyi incelemiştir.…”
Section: Introductionunclassified
“…This result was in line with previous studies that found higher BMI (body mass index) was predictive of higher total difficulties and emotional scores. 30,31 Adolescents with overweight will attract attention to their surroundings and often develop a poor self-image, which can lead to being bullied by their peers. 11 Thus, it may result in emotional problems among them.…”
Section: Discussionmentioning
confidence: 99%